History as trauma and the possibility of the future: Theo Angelopoulos' Voyage to Cythera. Issue 1 (1st April 2019) - Homer, Sean
Theo Angelopoulos has described Taxidi sta Kythira (Voyage to Cythera) (1984) as an attempt to 'exorcise the past' and offer the Greek audience a possibility to face the future without the traumas of the past. This article explores the question of the extent to which we can exorcise the past and asks if a future is possible without acknowledging the traumas of the past. Drawing upon cultural trauma theory, the article analyses the Greek Civil War (1946‐49) as a cultural trauma for the Greek Left, especially concerning the recognition of political prisoners and exiles. Psychoanalytic theory, on the other hand, suggests that a fundamental characteristic of trauma is the un-representability of the event itself, as a traumatic event is only known through its persistent reiterations. Through its multi-layered narrative structure and aesthetic strategies of deferral and displacement Voyage to Cythera stages the trauma of the Greek Civil War for both the returning exiles and the generation that followed. As a representation of presence through absence, the article considers Voyage to Cythera in terms of Thomas Elsaesser's concept of the parapractic text and Max Silverman's notion of palimpsestic memory whereby the film does not exorcise the past as such but reveals a past haunting the present. The article concludes with the reflection that a traumatic past has a tendency to return however much we may wish to lay it rest.